2021
DOI: 10.1016/j.celrep.2021.109833
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics atlas of oral 13C-glucose tolerance test in mice

Abstract: Highlights d A systems-level organ-specific metabolomics atlas of mouse tissues d 13 C 6 -glucose tracer tissue distribution during glucose tolerance test d Interactive online application for metabolic pathway exploration d LC-MS data resource covering polar metabolites and complex lipids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The first hypothesis is that the influx into the muscle glycolytic system does not increase as much as the blood glucose levels. A recent study showed that the influx of orally administered labelled glucose into the glycolysis of gastrocnemius muscle (white muscle), which was used in this study, is much smaller than that of soleus muscle (red muscle) 28 . The second hypothesis is that the efflux of glycolysis increased by activation as much as the influx.…”
Section: Discussionmentioning
confidence: 96%
“…The first hypothesis is that the influx into the muscle glycolytic system does not increase as much as the blood glucose levels. A recent study showed that the influx of orally administered labelled glucose into the glycolysis of gastrocnemius muscle (white muscle), which was used in this study, is much smaller than that of soleus muscle (red muscle) 28 . The second hypothesis is that the efflux of glycolysis increased by activation as much as the influx.…”
Section: Discussionmentioning
confidence: 96%
“…Using this same technology, we also illustrate that glucose uptake and oxidation is reduced in a model of DIO, which accurately reflects an IR phenotype. Overall, the utility of stable isotopes is becoming prevalent for metabolic fate mapping ( Buescher et al, 2015 ; Jang et al, 2018 ; Lopes et al, 2021 ; Diehl et al, 2022 ; Pachnis et al, 2022 ) and clinical diagnostics ( Modak, 2007 ; Braden, 2009 ), and we demonstrate that use of 13 C-glucose faithfully recapitulates metabolic deregulation in models of lung tumor progression and DIO.…”
Section: Introductionmentioning
confidence: 69%
“…Only the CATEGORY and CLASS levels are labeled to optimize space use and prevent overlapping labels. The Cytoscape network was built to visualize the quantitative data and statistics …”
Section: Methodsmentioning
confidence: 99%